Pemaknaan Representasi Laut dalam Anime Shiroi Suna no Akuatōpu - Restu Maulana Yusup; Marisa Rianti Sutanto; Ethel Deborah Lewerissa; Jessica Priscilla Nangoi (IZUMI, 2025)
In Japan, which is an island nation, the sea is important. The sea is also considered an element rich in meaning and full of mystery. This can be reflected in works of fiction, including anime. This study aims to analyse how the anime Shiroi Suna no Akuatōpu presents the sea through Japanese cultural beliefs and values that are closely related to the existence of kami (nature spirits in Japanese belief) using Roland Barthes' semiotics method. In Barthes' analysis, anime, like movies, are treated as texts that can be read and interpreted. Text or images are a system of signs that serve to shape meaning. The representation of the sea is examined through story elements and characterizations based on semiotic analysis involving signifier, signified, denotation, connotation. The sea in the anime Shiroi Suna no Akuatōpu functions as an important signifier that symbolizes the emotional journey of the two main characters, Kukuru and Fūka. Ultimately, the sea represents a myth realized through the spiritual experiences of the characters and the story. This research emphasizes the importance of the sea reflected through Japanese popular culture as a symbol of change and the relationship between humans and nature. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor